1999
DOI: 10.1177/096368979900800409
|View full text |Cite
|
Sign up to set email alerts
|

Bioartificial Endocrine Pancreas (Bio-AEP) for Treatment of Diabetes: Effect of Implantation of Bio-AEP on the Pancreas

Abstract: Recently, we described a diffusion chamber for a bioartificial endocrine pancreas (Bio-AEP). Pancreatic islet cells in the Bio-AEP device were isolated from the immune system of the host by an artificial barrier, while nutrients, electrolytes, oxygen, and bioactive secretory products were exchanged across this barrier. This experiment was designed to evaluate whether the diffusion chamber could be useful as a Bio-AEP in the treatment of diabetes. Six streptozotocin (STZ)-induced diabetic rats each received a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…In this study, it was possible to transplant mouse b cells into rats using Bio-AEP. This result was in agreement with those reported in previous studies [7,8]. Edamura et al (2004) reported pancreatectomized dogs could be transplanted with porcine pancreatic endocrine cells in a Bio-AEP [3].…”
supporting
confidence: 83%
See 1 more Smart Citation
“…In this study, it was possible to transplant mouse b cells into rats using Bio-AEP. This result was in agreement with those reported in previous studies [7,8]. Edamura et al (2004) reported pancreatectomized dogs could be transplanted with porcine pancreatic endocrine cells in a Bio-AEP [3].…”
supporting
confidence: 83%
“…We became interested in these reports on the Bio-AEP, since we thought it might improve -Note-sexual dysfunction induced by neuroendocrine dysfunction [11,13,19,21] based on hyperglycemia and insulin insufficiency. In addition, the Bio-AEP may make possible transplantation of b cells from different species because the Bio-AEP shows promise for long-term xenotransplantation without immunosuppression [7,8]. Therefore, the object of our study was to confirm whether or not mouse b cells could improve hyperglycemia and sexual dysfunction caused by diabetes mellitus.…”
mentioning
confidence: 99%
“…The structure of the Bio-AEP used in this study has previously been reported [5,10,26]. Briefly, the Bio-AEP used here was constructed with a silicon ring (4 cm in diameter and 0.5 cm thick) and two selectively semi-permeable membranes (0.1 µm pore size and 10 µm thick; Nuclepore Co., Pleasanton, California, U.S.A.) (Fig.…”
Section: Bio-aepmentioning
confidence: 99%
“…Within the chamber, PE-cells were cultured threedimensionally in synthetic extracellular matrix (ECM). The composition of the ECM was 1.0% agarose (Nacalai Tesque, Kyoto, Japan), 0.005% maltose-carrying polystyrene, 10 mM nicotinamide (Nacalai Tesque), and 0.15 mg/ ml type-I collagen treated to reduce the antigenicity (Cellmatrix I LA; Nitta Gelatin Co., Osaka, Japan) [5,10,26,28,29].…”
Section: Bio-aepmentioning
confidence: 99%
See 1 more Smart Citation